Enhancing Quantity and Quality Academic Papers through Collaborative Training Between Universitas Negeri Jakarta and Universitas Malaysia Sabah - Suherman, Suherman; Wibowo, Agus; Respat, Dwi Kismayanti; Utaminingtyas, Tri Hesti; Zairin, Gentiga Muhammad; Karyaningsih, Rr. Ponco Dewi; Gurendrawati, Etty; Sang, Lim Thien (Jurnal KARINOV, 2023)
Publikasi merupakan salah satu upaya untuk meningkatkan daya saing perguruan tinggi. Daya saing perguruan tinggi dapat dilihat dari jumlah publikasi ilmiah yang dihasilkan. Semakin produktif perguruan tinggi menghasilkan publikasi ilmiah, maka daya saingnya akan semakin tinggi. Kegiatan PKM ini merupakan salah satu tugas Tri Dharma dimana dosen dapat mengeksplor diri dan bersosialisasi dengan masyarakat. Kegiatan PKM bertujuan menambah pengetahuan dan pemahaman dosen tentang publikasi di jurnal internasional bereputasi. Kegiatan pelatihan ini dilaksanakan oleh Fakultas Ekonomi Universitas Negeri Jakarta (FEUNJ), dan Fakultas Bisnis, Ekonomi, dan Akuntansi Universiti Malaysia Sabah (FBEA UMS). Peserta kegiatan ini adalah dosen FEUNJ dan FBEA UMS. Hasil kegiatan ini menunjukkan peningkatan pengetahuan dan keterampilan para peserta pelatihan dalam menghasilkan artikel berkualitas internasional. Tulisanl ini dapat melengkapi literature yang sudah ada khususnya terkait dengan PKM kolaborasi internasional.. Kata kunci—Pelatihan penulisan artikel, Jurnal internasional bereputasi, Pengabdian kepdaa masyarakat Abstract Publication is one of the efforts to increase the competitiveness of higher education institutions. The competitiveness of tertiary institutions can be seen from the number of scientific publications produced. The more productive universities produce scientific publications, the higher their competitiveness. This community services activity is one of the Tri Dharma tasks where lecturers can explore themselves and socialize with the community. Community service activities aim to increase lecturers’ knowledge and understanding of publications in reputable international journals. This training activity was carried out by the Faculty of Economics, Universitas Negeri Jakarta (FEUNJ), and the Faculty of Business, Economics, and Accounting, Universiti Malaysia Sabah (FBEA UMS). The participants in this activity were lecturers at FEUNJ and FBEA UMS. The results of this activity show an increase in the knowledge and skills of the trainees in producing international-quality articles. This paper can complement the existing literature, especially related to international collaborative community services. Keywords—Training of article writing, International reputable journal, Community services activity.